Water reclaimation and reuse using vis-light responsive novel photocatalyst - Wong, Caleb Weng Kuan. (2012)
A hybrid system combining photocatalyst suspension irradiated with visible light and a low pressure submerged membrane module was used to purify water containing carbamazepine (CBZ). There was no chemical structure change for the membrane when it was irradiated under visible light emitting diode (vis-LED) light for 10 days. Highly alkaline solution induced chemical structure changes for the membrane, thus might influencing its surface hydrophilicity and hydrophobicity. The microfiltration (MF) membrane used in the study was found to be successful for separation of both P25 and our previously prepared C–N–S tridoped TiO2 (T0.05-450) particles as the turbidity of permeate water were consistently <0.1 NTU. TMP increased in the first 120 min for all TiO2 dosages investigated, and then remained almost constant. The steady–state TMP for the case with a higher TiO2 dosage was higher than the case with a lower TiO2 dosage. This could be attributed to the thicker porous cake layer for the higher TiO2 dosage. After the slight increase of TMP in the first 120 min, the steady–state TMP was achieved for all the solution pH investigated. The lowest steady–state TMP was found at pH 6 because the TiO2 particle was the largest. The TiO2 cake layer could be easily removed by water rinse, and the reinstated TMP operated at different permeate fluxes were close to the initial value. CBZ photocatalytic degradation efficiency was higher for the case with longer HRT (lower permeate flux), which allowed a longer reaction time of CBZ in the photoreactor. The CBZ removal rate and efficiency increased with the T0.05–450 dosage. However, P25 exhibited a much lower visible–light photocatalytic activity which could be attributed to its poor visible–light absorbance. Higher visible–light intensity and alkaline condition enhanced the CBZ photocatalytic degradation. The sMPR has the potential to be used for the removal of organic pollutants in a more cost effective way.